The Andean Pastoral Institute. A service to the Church of the South Andean - Gallego, Andrés (1984)
The Second Vatican Council had enormous significance for the present and the immediate future of the life of the Church. The gap between the "modern world" (European, Western) and a Church anchored in the past was too great. John XXIII was aware of the need to "open the windows of the Church" so that the outside air could penetrate.